Metagenomic Analysis of Tick-Borne Viruses in Hulunbuir, Inner Mongolia, China: Epidemiological Risk of Potential Novel Pathogenic Viruses Relevant to Public Health - You Zhang; Xiuying Tian; Ruoyan Peng; Gaoyu Wang; Wanxin Deng; Yibo Jia; Cheng Tang; Yi Huang; Xiaoyuan Hu; Chuanning Tang; Zihan Li; Jasper Fukwoo Chan; et al. (Zoonoses)
Inner Mongolia, with its vast grasslands providing ideal habitats for ticks, has recently emerged as a hotspot of novel tick-borne virus (TBV) prevalence. However, the diversity of TBVs and their potential spillover risks remain to be elucidated. In 2021, we collected 500 Haemaphysalis longicornis , Ixodes persulcatus , and Dermacentor silvarum ticks from Hulunbuir, Inner Mongolia, and conducted virome analysis and viral surveillance to evaluate TBV exposure risk in Hulunbuir. A total of 26 viral species belonging to nine families were identified, including four novel viruses (Yiliekede tick virus 1 [YLTV1, Rhabdoviridae ], Meitian tick virus [MtTV, Phenuiviridae ], Wunuer pestivirus, and Wunuer tick phlebovirus) and 11 new strains of human-pathogenic viruses (including Songling virus [SGLV], Beiji nairovirus [BJNV], and Nuomin virus [NOMV]), from three dominant tick species. Virome profiling revealed striking species-specific patterns: I. persulcatus exhibited the highest viral richness and abundance, dominated by Chuviridae (NOMV) and Phenuiviridae ; D. silvarum uniquely carried Phenuiviridae (MtTV); and H. longicornis showed Nairoviridae predominance (SGLV, BJNV). Phylogenetic analyses demonstrated that MtTV clustered with human-pathogenic Tacheng tick virus 2, and NOMV-YL strains showed high similarity to clinical NOMV isolates from febrile patients. Regional surveillance demonstrated MtTV’s pan-regional circulation in D. silvarum across nine locations (MIR=4–8%), contrasting with localized Yiliekede foci for SGLV (MIR=0.6%), BJNV (0.4%), and NOMV (1.0%). This study not only mapped the landscape of TBVs in a key pastoral region, but also highlighted the potential spillover risk of TBVs, including MtTV, YLTV1, SGLV, BJNV, and NOMV. Our findings underscore the urgent need for One Health strategies for monitoring emerging TBVs at the tick-human-livestock interface in northern China.